Питома поверхня, розміри кристалітів AlB12-nano продуктів взаємодії "BN-Al" у вакуумі - Петрова, В. А.; Гарбуз, В. В.; Муратов, В. Б.; Карпець, М. В.; Силінська, Т. А.; Кузьменко, Л. Н.; Терентьєва, Т. Н.; Васильєв, А. А.; Мазур, П. В.; Хомко, Т. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
Boron carbide (BC, B15-xCx B4C) has a unique combination of properties. This makes it a material for priority applications for a wide range of engineering solutions. The high melting point and heat resistance of the compound contribute to its use in refractory conditions. Due to its extreme abrasion resistance, B4C is used as an abrasive powder and coating. Due to its high hardness and low density, B15-xCx has ballistic characteristics. It is usually used in nuclear programs as an absorbent of neutron radiation Boron carbide ceramics (B15-xCx or BC) may lose strength and toughness due to the amorphization effect under high shear stresses. Aluminum dodecaboride AlB12 or B12Al, as well as boron carbide B12 [(CCC) x (CBC) 1-x] have common structural units B12 family of boron-icosahedral structures. The bond between icosahedrons is mainly due to atoms (Al, Si, O) or chains (CMC), where M is Al, Si, B, C. Doping BC powder with a small amount of AlB12, in cases of shock-shear stress, triggers the mechanism of "micro-cracking". Micro cracks and pores are formed in ceramics. The breakdown voltage decreases. AlB12 synthesis is associated with known difficulties. On the other hand. The production of metal-ceramic materials for several decades is associated with the interaction of liquid aluminum and boron nitride. The calculation of this reaction shows that it is exothermic. Avoiding oxidation in vacuum, the reaction occurs through the formation of aluminum nitride and aluminum dodeca-boride. In contrast to the liquid state, the process continues until the end, at conditional temperatures of evaporation of aluminum with slight changes in vacuum. The reaction product is a mixture of nanosized AlN/AlB12 powders with a weight ratio of 3/1 ready for baking without grinding. The acid-base properties of the nanosized powder mixture AlN + AlB12, the products of the interaction BN + Al in vacuum, which are used optionally, emit separate in pure phases of aluminum nitride and aluminum dodeca-boride. The yield of AlB12 is ~ 25%, boron reaches ~ 100%. The average particle size of the AlB12 powders according to TEM and ACS X-rays (area of coherent X-rays scattering), L (nm) is LTEM=110-150nm, LACS=51-70nm. The average specific surface area of the powder according to BET, TEM and ACS, SBET.m2/g=21,0-15,0; STEM.m2/g=21,4-15,4; SACS.m2/g=46,1-33,6; (at 1460 and 1640K, respectively).